Lessons Lessons on Refusal in Anthropology: Mauro Almeida and the Task of Permanent Decolonization of An(thropo)logical Thought - Cariaga, Diogenes Egidio (Cadernos de Campo (São Paulo, 1991), 2024)
As the author himself announces, unsuspecting individuals might find the heterogeneous gathering presented here strange, but Mauro Almeida is generous in guiding us through a reading program capable of connecting his reflections over the past decades, of a sophisticated intellectual who nonetheless views the world from the battleground of political struggles for socio-environmental rights with rubber tappers, riverine dwellers, and indigenous peoples in the Amazon Rainforest. Among the potential lessons to be gleaned from the reading of the work, there is the refusal of an anthropology that does not position itself adjacent to politics, where ontological wars do not separate "theory from practice."